Comparison of a Novel Human Rabies Monoclonal Antibody to Human Rabies Immunoglobulin for Postexposure Prophylaxis: A Phase 2/3, Randomized, Single-Blind, Noninferiority, Controlled Study. (15th September 2017) - Gogtay, Nithya J; Munshi, Renuka; Ashwath Narayana, D H; Mahendra, B J; Kshirsagar, Vikas; Gunale, Bhagwat; Moore, Susan; Cheslock, Peter; Thaker, Saket; Deshpande, Siddharth; Karande, Sunil; Kumbhar, Dipti; et al.
Abstract : Rabies virus neutralizing activity (RVNA) elicited by an antirabies human monoclonal antibody-containing postexposure prophylaxis (PEP) regimen was noninferior to RVNA produced by human rabies immunoglobulin–containing PEP in patients with category III suspected rabies exposure. Abstract: Background: Lack of access to rabies immunoglobulin (RIG) contributes to high rabies mortality. A recombinant human monoclonal antibody (SII RMAb) was tested in a postexposure prophylaxis (PEP) regimen in comparison with a human RIG (HRIG)–containing PEP regimen. Methods: This was a phase 2/3, randomized, single-blind, noninferiority study conducted in 200 participants with World Health Organization category III suspected rabies exposures. Participants received either SII RMAb or HRIG (1:1 ratio) in wounds and, if required, intramuscularly on day 0, along with 5 doses of rabies vaccine intramuscualarly on days 0, 3, 7, 14 and 28. The primary endpoint was the ratio of the day 14 geometric mean concentration (GMC) of rabies virus neutralizing activity (RVNA) as measured by rapid fluorescent focus inhibition test for SII RMAb recipients relative to HRIG recipients. Results: One hundred ninety-nine participants received SII RMAb (n = 101) or HRIG (n = 98) and at least 1 dose of vaccine. The day 14 GMC ratio of RVNA for the SII RMAb group relative to the HRIG group was 4.23 (96.9018% confidence interval [CI], 2.59–6.94) with a GMC of of 24.90 IU/mL (95% CI, 18.94–32.74) for SII RMAb recipients and 5.88 IU/mL (95% CI, 4.11–8.41) for HRIG recipients. The majority of local injection site and systemic adverse reactions reported from both groups were mild to moderate in severity. Conclusions: A PEP regimen containing SII RMAb was safe and demonstrated noninferiority to HRIG PEP in RVNA production. The novel monoclonal potentially offers a safe and potent alternative for the passive component of PEP and could significantly improve the management of bites from suspected rabid animals. Clincical Trials Registration: CTRI/2012/05/002709.